Organic Residues and Their Effect on Selected General of Autotrophic and Heterotrophic Soil Bacteria - Azzouz, A.A.; Hraib, S. O. (Al-Mukhtar Journal of Sciences, 1992)
The population of total soil bacteria increased in response to added organic amendments. Results obtained reflect the impact of C:N ratio of the residue on the degree of its influence. An/hun- dred-fold increase in total soil bacteria after one week of observed incubation in samples received wheat-straw or dry- manure. Alfalfameal amended samples showed a mush higher values and reached ten thousands-fold after two weeks of incubation. The heterotrophic, non-symbiotic ni- trogen-fixing bacterium of the genus Azotobacter responded effeciently to wheat-straw. An increase in their num bers by ten-thousands-fold was observed throughtout the incubation period. No response was detected with alfalfa-meal or dry-manure except after four days of incubation where the numbers increased by a hundred-fold, afterwhich a draw- back to the original values was seen. This could be due to the inhibition ac- tion of mineralized nitrogen (ammonium + nitrite + nitrate) which reached val- ues in excess of 200ppm in alfalfa-meal amended samples and by the antagones- tic effect of protein-decomposing bacte- ria that proliferate successfully in sam- ples recieved drymanure. The autotrophic nitrifiers (Nitrosomonas, Nitrobacter), behaved just-like the total soil bacteria in re- sponse to all organic amendments. The numbers increaed by ten-fold in wheat- straw or drymanure amended samples and reached a hundred-fold in al-falfa- meal treatment.